2012
DOI: 10.1007/s10562-012-0818-0
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch Synthesis: Preconditioning Effects Upon Co-Containing Promoted and Unpromoted Catalysts

Abstract: In the preparation and evaluation of FischerTropsch (FT) catalysts, active catalysts formed by both incipient wetness impregnation (IWI) and atomic layer deposition (ALD) of major components were demonstrated. ALD-deposited Co on a silica support was more effective than a similar catalyst deposited upon a support of ALD-deposited Al 2 O 3 on silica. The addition of Co reduction promoters including Pt, Ir and Ru using either ALD or IWI has been shown to strongly affect the catalyst pre-conditioning step. CO con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…These results clearly show that the reduction behavior of Co 3 O 4 strongly depends on the CeO 2 synthesis method, dispersion state of CoO x , and the interaction between CoO x and CeO 2 , which is consistent with conclusions of previous reports [26,43]. For the Co/CeO 2 catalysts, the reduction peaks can be classified as follows: (1) [41,42]. Among these catalysts, Co/CeO 2 -h displayed the lowest reduction temperature, which indicates that Co/CeO 2 -h exhibits the best redox performance.…”
Section: H 2 -Tpr and O 2 -Tpd Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…These results clearly show that the reduction behavior of Co 3 O 4 strongly depends on the CeO 2 synthesis method, dispersion state of CoO x , and the interaction between CoO x and CeO 2 , which is consistent with conclusions of previous reports [26,43]. For the Co/CeO 2 catalysts, the reduction peaks can be classified as follows: (1) [41,42]. Among these catalysts, Co/CeO 2 -h displayed the lowest reduction temperature, which indicates that Co/CeO 2 -h exhibits the best redox performance.…”
Section: H 2 -Tpr and O 2 -Tpd Analysissupporting
confidence: 91%
“…Similarly, all the samples display β peaks at about 800 • C due to the reduction of bulk CeO 2 , and it can be observed that the temperature of the reduction peak decreases gradually in the order 4%Co/CeO 2 -h< 4%Co/CeO 2 -p < 4%Co/CeO 2 -c. This further confirms that 4%Co/CeO 2 -h exhibits the best reduction performance among all catalysts and that strong interactions between the active component CoO x and CeO 2 supports are present. Various studies [40][41][42] have shown that the reduction of Co 3 O 4 is a two-step process, involving the reductions of Co 3 O 4 to CoO and CoO to Co. These results clearly show that the reduction behavior of Co 3 O 4 strongly depends on the CeO 2 synthesis method, dispersion state of CoO x , and the interaction between CoO x and CeO 2 , which is consistent with conclusions of previous reports [26,43].…”
Section: H 2 -Tpr and O 2 -Tpd Analysissupporting
confidence: 90%
“…The first section demonstrates how these uncertainties were overcome by coupling XANES and EXAFS spectroscopies to temperature programmed reduction/carburization [32][33][34][35][36][37][38][39][40]. The influence of catalyst preparation [39][40][41][42][43][44] and pretreatment [37,44,45] on activation is also addressed to some extent in this section. The working state of unpromoted catalysts has also been investigated by EXAFS [e.g., 56].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, researchers have examined -using EXAFS and XANES spectroscopies -the impact of the promoter on the extent [57][58][59][60] or both rate and extent [7,34,39,61,62] of reduction of cobalt oxides simply by focusing on changes at the Co edges. Researchers have also explored the carburization of iron oxides by examining Fe edge data [35,36,38,62].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bambal et al [22] added chelating agents such as nitrilotriacetic acid and ethylenediaminetetraacetic acid to silica, which modified the surface prior to adding cobalt nitrate; the resulting dispersions were improved by 2-4.3 times. Another example was the use of atomic layer deposition (ALD), which enabled a decrease in the size of Co particles from 10.1 nm to the range of 5.6-5.9 nm for Co/silica catalysts with Co loadings in the range of 20-25% [23].…”
Section: Introductionmentioning
confidence: 99%